Gränser för polisiär innovation – rättssäkerhet, enhetlighet och demokratisk legitimitet - Lena Landström; Markus Naarttijärvi (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The literature on policing asserts that there has been a remarkable emphasis on innovation in police work over the last decades. During the same time, police organizations in several countries have been centralized to promote increased unity and response to political steering and method development. In Sweden, the police reform was motivated by a perceived correlation between uniformity in working methods and organizational effectiveness. From a legal perspective, innovation in police methods involves inherent questions of rule of law – ensuring legality, compatibility with human rights, and predictability for citizens. This also carries implications for democratic legitimacy, since the police have far-reaching power to interfere with citizens’ spheres of interest. This article discusses issues of innovation within the Swedish police from a rule of law and democracy perspective. Innovation in police work is discussed on a system level through a study of the legal framework and institutional conditions introduced with the creation of the new police organization. Results are presented from an interview study with police managers on different levels within the new organization. The results suggest that innovation in police work develops largely organically at different levels and units within the police organization and then spread as “best practices” which the new Police Authority is seen as organizationally able to pick up and disseminate. Secondly, police openness to new evidence-based methods from outside the organization is increasing. Thirdly, there is a tension between the increased ability to create uniformity in methods and the need to adjust these methods to local conditions. Lastly, some uncertainties regarding legal accountability seem to exist as new methods are developed and implemented.